COMPARATIVE ANALYSIS OF “TAZKIRAT USH-SHUARO” AND “SHAMI GHARIBON” - Makhfirat Kurbonalieva Sadullaevna (International Engineering Journal For Research & Development, 2022)
The article shows the commonalities of Tazkirat-ush-Shuaro with other tazkiras. Our aim is to introduce into the Persian-Tajik literature, on the one hand, the history of tazkiranavism and, on the other hand, the influence of Mutribi's tazkira on the tazkira of the later period. From this point of view, we have tried to compare the tazkirat of “Tazkirat ush-shuaro” by Mutribi Samarkandiy with the tazkira of Lachhami Nairoyin “Shomi gharibon”. Our observations have shown that the “Tazkirat ush-shuaro” tazkira is an important source in the study of not only the scientific, literary and cultural life of Movarounnahr, but also the literary environment of India. Although the author of “Shomi Gharibon” does not refer to the source, it has been studied that the influence of Mutribi's work “Tazkirat ush-shuaro” in the tazkira is significant.